Xanthoxyline prevents aging and neuronal damage by activating autophagy and DAF-16 expression in Caenorhabditis elegans - Hyemin Kim; Saebyeol Lee; Hak Kyun Kim; Sang-Kyu Park (Animal Cells and Systems)
Xanthoxyline, a plant-derived phytochemical, has anti-bacterial, anti-fungal, and anti-cancer activities. We intended to investigate the effect of xanthoxyline on the response to oxidative stress, aging, and Parkinson’s disease. The effects of dietary supplementation with xanthoxyline on stress response and aging were examined in vivo using Caenorhabditis elegans as a model system. Genetic analysis using mutants, RNAi, and quantitative RT–PCR was performed to identify underlying mechanism involved in xanthoxyline-induced longevity. Animal disease models were employed to examine the effect of xanthoxyline on Parkinson’s disease. Xanthoxyline increased resistance to the oxidative stress induced by H2O2. The mean lifespan of worms was significantly increased by supplementation with xanthoxyline. The lifespan-extending activity of xanthoxyline was not accompanied by reduced fertility. Xanthoxyline delayed the age-related decline in motility. Interestingly, the expression of two longevity-assuring genes, hsp-16.2, and sod-3, was increased by xanthoxyline supplementation. Genetic analysis suggested that lifespan extension by xanthoxyline was mediated by activation of autophagy and required DAF-16. In a model of Parkinson’s disease, degeneration of dopaminergic neurons was prevented by supplementation with xanthoxyline, in a manner dependent on DAF-16. Taken together, we concluded that xanthoxyline exerts an anti-aging activity, possibly by activating the DAF-16-dependent stress response, and reduces the risk of Parkinson’s disease, in a manner mediated by DAF-16. Xanthoxyline shows promise for the development of novel nutraceuticals against aging and Parkinson’s disease.